The Role TPF to Loan Defisit Ratio - Meini rotinsulu, Clara neltje (Journal of Management, 2023)
The purpose of this research is to look at the impact of Third Party Funds (TPF), Credit, and Capital Adequacy Ratio (CAR) on Loan to Deposit Ratio (LDR) at Rural Bank (BPR) Sulawesi Mandiri.  The purpose of this research is to determine how the composition of funds, lending, and the degree of capital adequacy of banks impact the loan to deposit ratio. The multiple regression analysis approach was utilised to examine BPR Sulawesi Mandiri  data from a certain time period. The findings indicated that third-party funds have a positive and substantial impact on LDR, implying that a rise in third-party funds and a non-significant BPR Sulawesi Mandiri  resulted in an increase in lending. Credit has a positive but small influence on LDR, indicating that an increase in bank lending will raise the loan-to-deposit ratio. Capital Adequacy Ratio has a negative but substantial influence on LDR, showing that the bank's capital adequacy level has little impact on lending policy. The study's implications include the need of effective fund and credit management in boosting BPR performance, as well as the need for continual capital policy assessment to support the banking sector's expansion.